A comprehensive comfort assessment method for indoor environmental quality in university open-plan offices in severe cold regions - Li, Zheng; Zhang, Qingwen; Fan, Feng; Shen, Shizhao (Building and environment, 2021)
This paper presents a comprehensive comfort assessment method for indoor environmental quality in university open-plan offices (UOROs) in severe cold regions based on the combination weighting method. The questionnaires for the fuzzy analytic hierarchy process (FAHP) method were firstly collected from 405 experts to obtain the subjective weighting scheme of UOROs. Then, the field measurements of four environmental factors of 22 UOROs were conducted and the corresponding 1352 questionnaire surveys on the subjects’ comfort were collected. The relationships between four comfort factors and indoor environmental parameters were obtained from the field studies, and the objective weighting scheme was calculated using the entropy method (EM). Based on the game theory, the combination weighting scheme was given via integrating the results of the FAHP method and EM. The comprehensive comfort index for UOROs was finally provided by combining factor weights and fitting formulas, and the rationality and correctness of the method were demonstrated via experimental verification. Furthermore, the comparison of the weighting schemes between this study and other studies was discussed and the results revealed that the requirements of researchers for the sound environment were higher than normal office workers. The comprehensive comfort assessment method in this study can help designers and users to improve building performance by adjusting indoor environmental parameters and also make them better balance the relationship between human comfort and energy use. •A comprehensive comfort assessment method for IEQ in UOROs was proposed based on the combination weighting method.•The rationality and correctness of the method were demonstrated via experimental verification.•Thermal environment and sound environment are the two most important aspects of researchers’ comfort in UOROs.•The acceptable ranges of different physical parameters were given based on field measurements and questionnaire surveys.